Methodology and device to obtain torsional shear strength of glued joints - Petrauski, Alfredo; Petrauski, Sandra Maria Ferreira Couri; Della Lucia, Ricardo Marius; Petrauski, Mateus Couri (Floresta, 2020)
This paper presents a methodology to obtain the shear strength of glued joints, at the torsion moment. In the current standards this strength is measured by compression tests. The device designed for this purpose are also presented. The motivation for this test is related to the possibility of execution of glued wooden structures with joints under bending moment, shear force and normal force simultaneously. It was admitted the hypothesis that the joint strength can be different depending on the test type. The methodology is relatively simple and in order to obtain the results classic equations from Mechanics of Materials were used. The strength results of 198 test specimens, tested by standard methodology, were compared, with an equal number of specimens made and tested with the proposed methodology, resulting in 396 tests. 208 specimens were glued with resorcinol-formaldehyde and 188 with castor oil-based adhesive. The wood used was Eucalyptus sp. The specimens were made according to seven series involving gluing with the following angles between the fibers: 0°, 15°, 30°, 45°, 60°, 75° and 90°. Regardless of the adhesive type, there was a significant difference for the strengths presented by the two methods. From the seven angles studied, it was noticed a difference in six of them, except for the 30° series. The compression shear strength was severely affected by the gluing angle, with increasing losses towards higher angles. On the contrary, the strength offered by the joints tested by torsion did not seem affected by the gluing angle. Keywords: wood; adhesive; characterization; procedure.